Diagnosis dan Tatalaksana Epistaksis: Tinjauan Literatur Terkini - Putri Alvina Sofia Adila Nafsih; Cut Elvira Novita (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Epistaxis, or more commonly known as nosebleeds, is one of the most frequently encountered medical emergencies in the field of ENT. Epistaxis is a condition in which blood flows from the nasal cavity. Although often considered a minor disorder, epistaxis can be a sign of a more serious medical condition, especially if it occurs repeatedly or in large amounts. Globally, the prevalence of epistaxis is estimated to be around 21.7%, with a wide range of variation between countries, namely between 3 and 60 cases per 100,000 population per year. This paper aims to review the aspects of diagnosis and management of epistaxis based on the latest literature. The method used in this study was a search and analysis of various scientific publications, guidelines, and relevant current journals. The discussion covers the identification of types and signs of epistaxis, emergency management, and tampon insertion strategies. Understanding the appropriate and rapid diagnosis and management is essential to prevent the condition from worsening.